Motivation at English Language Training Program - Budiana, Kartika Marta; Cahyaningati, Desi Tri; Aprillianita, Riski (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
This study investigates the motivation of elementary school teachers participating in an online English language training program as part of a community service activity. The objective of this study was to offer practical suggestions for educators and aspiring researchers who are interested in understanding and enhancing learners' motivation in English language training. Conducted with 50 teachers from 18 schools in Surabaya and 2 schools in Jakarta, Indonesia, the research employed a descriptive method using questionnaires and in-depth interviews. The findings highlight the importance of intrinsic, extrinsic, and avoidance motives in learners' participation. Stakeholders' demands and the intention to stay current with modern trends were identified as significant factors influencing motivation. The study emphasizes understanding learners' motivation to determine the success or failure of online English learning, noting that motivation serves as the driving force for acquiring a second language. The research also explores the impact of Computer-Assisted Language Learning (CALL) systems on learners' motivation, nothing their positive effects on interest, autonomy, and oral communication practice. The study aims to provide insights into the overall motivation of language learners, particularly in the context of CALL systems, to enhance language acquisition.